Different flavors of Toll guide olfaction. - Neyen, C.; Lemaitre, B. (Trends in Immunology, 2015)
Toll-like receptors are historically linked to immunity across animal phyla, but accumulating evidence suggests they play additional roles in neuronal networks and in cell-cell interactions. Ward and colleagues now identify Toll-6 and Toll-7 as instructive guidance cues during Drosophila olfactory development.